BERBAGAI KESALAHAN TATA LANGKAH PEKERJAAN LABORATORIUM KLINIK - Prihatini Prihatini (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
Laboratory procedure errors occurred in some cycle parts during prae-analytic, analytic and post analytic sessions, they must beexcluded and prevented in the process because the outcome would support the diagnosis of diseases also to enhance their confidence.The laboratory works were carried out in the right methods, is suppervised accurately base on haematological, microbiological, clinicalchemistry and immunological standard examinations. Any deviation although the procedure results according the standard one mustbe registered. Laboratory errors revealed must be monitored as the means to reduce errors and to threat them well. Beside it is necessaryto have a good communication between patients, doctors as well as with the laboratory services.